Protocol digest of a phase III trial to evaluate the efficacy of preoperative chemotherapy with S-1 plus oxaliplatin followed by D2 gastrectomy with postoperative S-1 in locally advanced gastric cancer: Japan Clinical Oncology Group study JCOG1509 (NAGISA Trial). (7th October 2022) - Mizusawa, Junki; Tokunaga, Masanori; Machida, Nozomu; Yabusaki, Hiroshi; Kawabata, Ryohei; Imamura, Hiroshi; Kinoshita, Takahiro; Nomura, Takashi; Nunobe, Souya; Tsuji, Kunihiro; Katayama, Hiroshi; Fukuda, Haruhiko; et al.
Abstract: In Japan, postoperative chemotherapy is a standard care for stage II/III gastric cancer after curative resection with D2 lymph node dissection, and the clinical outcomes of patients with stage III gastric cancer are unsatisfactory. A combination of oral S-1 and oxaliplatin, that is the standard chemotherapy regimen for unresectable advanced/recurrent gastric cancer associated with a high response rate, was considered the most promising preoperative chemotherapy regimen. This randomized phase III trial was started in September 2016 to confirm the superiority of preoperative chemotherapy with S-1 plus oxaliplatin followed by D2 gastrectomy with postoperative chemotherapy compared with D2 gastrectomy with postoperative chemotherapy for patients with clinical T3–4N1–3 M0 locally advanced gastric cancer in terms of overall survival. A total of 470 patients will be enrolled from 63 hospitals in Japan for 8.5 years. This trial has been registered in the Japan Registry of Clinical Trials as jRCTs031180350 [https://jrct.niph.go.jp/latest-detail/jRCTs031180350 ]. Abstract : A randomized phase III trial was started to confirm the superiority of the addition of preoperative chemotherapy to D2 gastrectomy with postoperative chemotherapy for patients with clinical T3–4N1–3 M0 gastric cancer.